ANALISIS DAN VISUALISASI DATA SAMSUNG SALES MENGGUNAKAN EXPLORATORY DATA ANALYSIS PADA TABLEAU - Putra, Yahya Nugraha; Wahyu, Ofel Idhan; Yovita, Kristian; Utomo, Pradita Eko Prasetyo (Department of Information System Muhammadiyah University of Riau, 2025)
The development of 5G technology has a significant impact on the mobile device industry, but its adoption is uneven in many regions. The study was conducted to analyze Samsung’s 5G device sales trends globally and examine the relationship between network infrastructure, consumer preferences and device sales performance. The method used is Exploratory Data Analysis (EDA) with the help of interactive visualization through Tableau. Secondary data is obtained from Kaggle and covers the period 2019–2024, with variables such as number of units sold, network coverage, 5G average speed, and preference score. Results show that about 65% of sales come from high preference models, and since 2021 5G devices have mastered more than 70% of the global market. In addition, the Galaxy S Series model recorded preference score above 85%, showing that consumer perception is highly influential on sales performance. Visualization in the form of dashboards supports strategic understanding of markets based on regions, products, and time. This EDA-based visualization is able to provide deep insight for policymakers and manufacturers in strategizing 5G market penetration strategies more effectively and sustainably